2004
DOI: 10.1002/jcb.10766
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids mediate differential anti‐apoptotic effects in human fibroblasts and keratinocytes via sphingosine‐1‐phosphate formation

Abstract: Glucocorticoids are potent anti-inflammatory and immunomodulatory drugs which also induce growth inhibition in a variety of cell types. For this reason long-term treatment of inflammatory skin diseases may result in irreversible skin atrophy. To elucidate whether the antiproliferative action of glucocorticoids in fibroblasts is accompanied by induction of apoptosis we investigated the influence of dexamethasone (DEX) on both parameters. Interestingly, we revealed that growth inhibitory concentrations of this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
2
25
0
2
Order By: Relevance
“…As documented by over 2200 publications in the PubMed database and summarized in numerous recent reviews, 5,[8][9][10][11][12][13] GC induce massive apoptosis in certain cells of the lymphoid lineage, particularly immature thymocytes and ALL cells, and the latter has been exploited in the therapy of lymphoid malignancies. 4 GC have further been reported to induce cell death (alone or in combination with other death inducers) in some nonlymphoid tissues and cells such as bone, 14 hippocampus, 15 eosinophils, 16 fibroblasts 17 and certain cancer cells. 18 Interestingly, GC support survival in erythroblasts, 19 neutrophils 20 and several nonhematologic tissues such as mammary gland, ovary, liver and fibroblasts (reviewed in Amsterdam and Sasson 21 ).…”
Section: Pleiomorphic Effects Of Gcmentioning
confidence: 99%
“…As documented by over 2200 publications in the PubMed database and summarized in numerous recent reviews, 5,[8][9][10][11][12][13] GC induce massive apoptosis in certain cells of the lymphoid lineage, particularly immature thymocytes and ALL cells, and the latter has been exploited in the therapy of lymphoid malignancies. 4 GC have further been reported to induce cell death (alone or in combination with other death inducers) in some nonlymphoid tissues and cells such as bone, 14 hippocampus, 15 eosinophils, 16 fibroblasts 17 and certain cancer cells. 18 Interestingly, GC support survival in erythroblasts, 19 neutrophils 20 and several nonhematologic tissues such as mammary gland, ovary, liver and fibroblasts (reviewed in Amsterdam and Sasson 21 ).…”
Section: Pleiomorphic Effects Of Gcmentioning
confidence: 99%
“…GCs are known inducers of apoptosis in numerous cell types, including thymocytes, eosinophils, neutrophils, hippocampal neurons, and proliferative chondrocytes (56 -60), and various malignancies of lymphoid origin and thus have become one of the most common therapeutic agents for leukemias and lymphomas (61). Interestingly, GCs have been described to exert an anti-apoptotic effect on epithelial ovarian or breast cancer cells, human glioblastoma, hepatoma, and fibroblasts (62)(63)(64)(65)(66). The antiapoptotic effect of GCs on keratinocytes is achieved through the concerted suppression of pro-apoptotic and induction of anti-apoptotic genes.…”
Section: Of Gc-regulated Genesmentioning
confidence: 99%
“…While NF-B inhibitors did not abolish the antiapoptotic effect, the sphingosine kinase inhibitor N,N-dimethylsphingosine did so. This effect is cell specifi c as it was not seen with keratinocytes [64] . Although we previously demonstrated that vitamin D 3 and the transforming growth factor-␤ stimulate fi broblast proliferation via an increased sphingosine phosphorylation [65,66] and S1P then activates Smad proteins [67] , the S1P-induced proliferation is obviously overrun by the antiproliferative effect of glucocorticoids due to the inhibition of IL-1 ␣ and IL-6 release [5] .…”
Section: Glucocorticoid Effects On the Skinmentioning
confidence: 87%